A study of faculty-librarian relationships in selected private colleges and universities in Greater Manila - Flores, Nancy D., 1949-
Although some 85 per cent of the total faculty respondents assist the librarians in developing the library collection, the extent and degree of faculty participation in the collections development program of the library leave much to be desired. Majority of the faculty respondents noted that their participation in the above-mentioned activity is only done "occasionally" as summarized in table 14. It is therefore indicated that librarians must find ways and means of securing adequate faculty participation in this vital task of the library.